2013
DOI: 10.29173/cais439
|View full text |Cite
|
Sign up to set email alerts
|

Making Choices: What Readers Say About Choosing Books to Read for Pleasure

Abstract: this paper analyses 194 open-ended interviews with committed readers who read for pleasure, focusing in particular on interviewees' responses to questions about how they choose and how the reject a book. The analysis suggests that a comprehensive model for the process of choosing books for pleasure-reading must include five related elements that are examined in the paper. . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…In this research, adults mediate and support children's autonomy in fostering long‐term and intrinsic motivation to read, with confidence (e.g. Ross, ), affect (e.g. Nell, ) and personal resonance (e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…In this research, adults mediate and support children's autonomy in fostering long‐term and intrinsic motivation to read, with confidence (e.g. Ross, ), affect (e.g. Nell, ) and personal resonance (e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…Similarly, Ross () refers to the “clues on the book itself used to determine the reading experience being offered” (p. 18).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of what effect a reader might want from reading a book in terms of the experience to match his or her mood was one of the key findings of Ross (), who offers a “model for the process of choosing a book for pleasure” (p. 16), which applies directly to public library users rather than to potential book consumers. Based on an analysis of readers’ statements, the model describes five interlinked elements, namely: Reading experience wanted: the “What mood am I in?” test. Alerting sources that the reader uses to find out about new books. Elements of a book that readers take into account in order to match book choices to the reading experience desired. Clues on the book itself used to determine the reading experience being offered. Cost in time or money involved for the reader in getting intellectual or physical access to a particular book (pp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almost by definition, participants on the Goodreads site are relatively committed readers. Ross () suggested that avid readers are an underutilized resource when it comes to understanding how readers successfully find their next book. Over a number of years, she and her students interviewed 194 committed readers, deliberately selected as “individuals who read a lot and read by choice” (p. 7).…”
Section: Avid Readers and Their Resources; Avid Readers As Resourcesmentioning
confidence: 99%
“…One question Ross () and her colleagues explored with these readers was how they locate reading material. The findings are illuminating even today, when many elements of our media culture have changed.…”
Section: Avid Readers and Their Resources; Avid Readers As Resourcesmentioning
confidence: 99%